Manipulating Strain in Transistors: From Mechanically Sensitive to Insensitive. (19th March 2022) - Li, Ming‐Zheng; Guo, Liang‐Chao; Liu, Gang; Yan, Yan; Zhang, Meng; Han, Su‐Ting; Zhou, Ye
Abstract: The rapid development of flexible and stretchable materials has portrayed a bright future of flexible electronics in pursuing the concept of "Internet of Things." Transistors, as one of the fundamental units in electronic devices, are being widely studied in exploring the possibility of increasing their flexibility and/or stretchability to fulfill the requirement in flexible electronics, from basic logic circuits to intelligent devices. However, the mechanical stimuli induced by bending and stretching activities can lead to unexpected performance degradations. Here, an in‐depth analysis of approaches to modulating the sensitivity of flexible and stretchable transistors, from a mechanically sensitive type to an insensitive type is demonstrated. Starting with the structural design, the mechanism of sensitivity modulation is explicitly analyzed, such as effects based on the modulation of dielectric capacitance, conductance of active channels, or contact resistance at interfaces in sensitive transistors and strain patterning technology applied to an insensitive type. The sensitivity modulation for transistors is further analyzed regarding material utilization based on different dimensional forms. Finally, the potential applications where flexible and stretchable transistors can be employed as an outlook are discussed. Abstract : Deformation‐induced strain has become an inevitable problem for flexible and stretchable transistors and hinders the stable performance of flexible electronics in applications. A series of methods to optimize transistors' performance under different strains have been proposed. This review on the state‐of‐the‐art approaches is presented to manipulate the strains inside transistors, from delicate structural designs to rational material utilizations.